Analysis of Technology Involvement in Islamic Religious Education Learning - Unik Hanifah Salsabila; Rosyada Ayu Fatimah; Riska Anisa Indriyani; Fuad Dirahman; Yuhan Anendi (Borneo Educational Journal (Borju), 2023)
The utilization of new technologies in Islamic educational practices is an undeniable necessity at this time. This article analyzes how Islamic religious education utilizes technology in the teaching and learning process, as well as the difficulties related with implementing this technology. This study employed a qualitative research approach in the form of a literature review to collect its data. According to the research findings, technology serves multiple functions and contributes to a variety of Islamic religious education components. This includes evaluation tools, transmission media, and design and planning forums for learning. Other findings explain some of the obstacles teachers face when utilizing technology, such as the need for more technological skills and infrastructure. On the basis of this study's findings, recommendations have been developed to enhance teachers' and students' understanding of how to maximize available technology by engaging in an intensive learning process. Keywords: engagement; Islamic education; learning technologies